(untitled) (Journal of the Medical College for Women & Hospital, 2026)
The incidence of gunshot injuries to long bones is growing, and orthopedic surgeons should be more aware of the treatment and consequences of these injuries. Various treatment modalities are there to manage these types of gunshot-induced open long bone fractures. High-energy firearm injuries to the tibia are especially complex due to the bone’s subcutaneous location, predisposing it to extensive soft tissue damage, contamination, and delayed union. Most interventions involve staged surgery that is temporary stabilization with external fixator followed by meticulous wound management. After satisfactory wound care, definitive fracture fixation is performed through various types of implants, like- plates or intramedullary nails in the subsequent surgery. Sometimes, primary internal fixation is possible by timely and meticulous wound debridement followed by regular wound dressing and appropriate antibiotics. Here we report the case of a 24-year-old male who sustained a high-energy gunshot injury to the right upper leg during a political conflict. The projectile caused an open comminuted proximal tibial fracture with sizable entry and exit wounds. Initial management included hemorrhage control, broad-spectrum antibiotics, urgent debridement, and limb immobilization. Culture-guided antimicrobial therapy and supportive care were provided. Once a healthy granulating wound bed was achieved, definitive internal fixation with a locking plate was performed on day 10. The patient’s postoperative recovery was uneventful, showing gradual wound healing and radiographic callus formation. This case underscores the importance of prompt debridement, appropriate anti-biotherapy, and timely stabilization in managing Gustilo IIIA open tibial fractures caused by gunshot injuries. Multidisciplinary care and staged surgical intervention play a critical role in optimizing outcomes, thus avoiding multiple operations in such high-energy firearm-associated limb trauma. J Med Coll Women Hosp.2026; 22(1): 165-171